PENANGANAN KETIDAKAKURATAN CATATAN INVENTARIS PADA GUDANG DIVISI INFRASTRUKTUR PERHUBUNGAN PT PINDAD - Nadya Allyssia Putri; Mohammad Benny Alexandri; Tribowo Rachmat Fauzan (POLITEKNIK LP3I JAKARTA, 2024)
The Transportation Infrastructure Division of PT Pindad is responsible for the management and distribution of materials and components necessary for the company's production and operations. However, this Division often faces issues with inventory record inaccuracies. This inaccuracy occurs due to a discrepancy between the actual stock in the Warehouse and the data in the SAP ERP system. This research aims to analyze the inventory records in the Warehouse of the Transportation Infrastructure Division of PT Pindad using a qualitative descriptive approach method. The results of this study, through fishbone diagram analysis, show that the main cause of inventory record inaccuracies is employees not reserving materials through the ERP SAP system and the absence of SOPs regulating material reservations. As a solution, it is recommended to design Standard Operating Procedures (SOP) for the production material request (reservation) process through the ERP SAP system, which includes stages from the production department's material request, inventory management by the Warehouse, to the storage of finished goods back in the Warehouse after the production process is completed.